A Organização Seqüencial da Resenha Crítica - Machado, Anna Rachel (The ESPecialist, 2012)
This article aims at presenting some theoretical reflection on the sequential organisation of critical reviews. Our proposal is that such reviews may be considered as being basically organised under the form of a descriptive sequence, as defined by Adam (1992). This proposal is based on the elaboration of the categories that define descriptive sequences, and their comparison with the operations suggested by Beacco & Darot (1984) for the analysis of film reviews and summaries. These ideas are considered a suitable tool for the teaching of review analysis and their production.